RNA 2D Structure Prediction: A review (Sciences & Technologie. C, Biotechnologies, 2016)
RNA, a macromolecule that provides several biological functions: gene translation into proteins, regulation of gene expression, prediction of 3D structure and RNA function, etc. In this work, we will review the prediction of RNA secondary structures by dynamic programming based on the classical Nussinov algorithm. We took into account four possible links between the nucleotides forming the RNA polymer chain (canonical GC, CG, AU AU bonds, wobble bonds: GU or UG, etc.). The program tested in this work shows that the developed algorithm correctly predicts the different base pairs that enter the 2D structure of the RNA.